The genomic characterization of the South African Bonsmara using whole-genome sequencing data - Van Marle-Koster, Este (University of Pretoria, 2024)
Dissertation (MSc Agric Animal Science(Animal Breeding and Genetics))--University of Pretoria, 2024.